O direito à informação e as responsabilidades decorrentes da relação entre o médico e o paciente. - Maia, Maurilio Casas (2011)
The purpose of this study was to assess the extent necessary information to make valid informed consent, legitimizing the medical act. The theme was due to the increasing importance of the right to information for both the effect of patient consent as to examine the liability of the physician. Therefore, it was essential to assess the extent and quality information will be passed on to the patient if the information content will be determined by a standard real patient or a patient abstract, or if the doctor can select the information to its discretion. To achieve this goal, we studied the historical issues of informed consent and medical liability, the fundamental principles and rights incident on the medical relationship, as well as the essential characteristics thereof. Since then analyzed the formative elements of informed consent, informed consent to enter only after the scope of medical liability. We used the method of inductive approach because it is coming from private institutions, we attempted to form a general rule for the extension of medical information. Tanger in the methods of procedure, we adopted the functionalist and the historical method, because the development of institutes related to the problem under study and its goals are basic to the conclusion of this work. Finally, with regard to research techniques were adopted to bibliographical and documentary research, based primarily on the doctrine and jurisprudence. In conclusion, it was felt that information should be provided in accordance with standard concrete patient under penalty of civil liability of the doctor, this mainly because of the principle of real equality in the medical relationship, forcing theThe aim of this study was to assess the extent necessary information to make valid informed consent, legitimizing the medical act. The theme was due to the increasing importance of the right to information for both the effect of patient consent as to examine the liability of the p trader to observe the ability of understanding of each patient.